2013
DOI: 10.1186/1471-2431-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Association between iron status, iron deficiency anaemia, and severe early childhood caries: a case–control study

Abstract: BackgroundSevere tooth decay is known to affect the health and well-being of young children. However, little is known about the influence of Severe Early Childhood Caries (S-ECC) on childhood nutritional status. The purpose of this study was to contrast ferritin and haemoglobin levels between preschoolers with S-ECC and caries-free controls.MethodsChildren were recruited as part of a larger case–control study examining differences in nutritional status between those with and without S-ECC. Preschoolers with S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 8 publications
5
136
1
11
Order By: Relevance
“…Furthermore, Means and Krantz [1992] stated that chronic inflamma- tion from pulpitis and chronic dental abscess of untreated severe caries affects growth via chronic inflammation. Schroth et al [2013c] reported that children with S-ECC appear to be at significantly greater odds for iron deficiency and iron deficiency anemia than cavity-free children. Children living in low socioeconomic situations may also not be able to regularly go to the dentist and use dental floss or fluoride toothpaste to prevent dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Means and Krantz [1992] stated that chronic inflamma- tion from pulpitis and chronic dental abscess of untreated severe caries affects growth via chronic inflammation. Schroth et al [2013c] reported that children with S-ECC appear to be at significantly greater odds for iron deficiency and iron deficiency anemia than cavity-free children. Children living in low socioeconomic situations may also not be able to regularly go to the dentist and use dental floss or fluoride toothpaste to prevent dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Dental caries can result in various detrimental effects on children, including pain, failure to thrive, poor nutritional status, and behavioral problems. [2][3][4][5][6] Early preventive dental care has been demonstrated to prevent dental disease when administered within the first year of life. 7 Evidence also indicates that children who receive early preventive dental care are less likely to require subsequent restorative or emergency treatment 7 and have lower dental-related health care costs, particularly among high-risk populations.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…However, studies that have related malnutrition or micronutrient deficiencies to dental caries in the primary dentition offer indirect evidence of this association [19][20][21][22]. In contrast, some studies suggest a cariogenic effect of micronutrients [6,8].…”
Section: Discussionmentioning
confidence: 99%